The socio-economic impact of land restoration on Masha community of Kalkfontein, in Mpumalanga Province, South Africa - Tshivhase, Fhatuwani Thomas (University of Limpopo (Turfloop Campus), 2007)
The study deals with the socio-economic impact of land restoration on the Masha Community. Members of Masha Community opted to relocate to their ancestral land, Kalkfontein, which they successfully reclaimed in the year 2000. The study interrogates if the restoration of land to the Community has made any positive impact on their social and economic well being. It focuses on the key challenges posed by land restoration to both the Community and the different spheres of government. It also deals with the challenges of leadership among the Masha Community which are threatening the attainment of developmental goals at Kalkfontion. The study concludes by making some concrete proposals and recommendations on how the State, the Community and various developmental agencies could resolve the problems faced by Communities such as the Masha after their land has been restored.
Thesis (M.Dev.) --University of Limpopo, 2007
Keywords: Socio-economic impact; Land restoration; 333.310968; Blacks -- Relocation -- Social conditions; Blacks -- Relocation -- South Africa